(untitled) (Communicare: Journal for Communication Studies in Africa, 2022)
In 2004, Daniel Hallin and Paolo Mancini published a landmark work of media theory entitledComparing media systems: three models of media and politics. The theory, like the models itmakes use of, has a high degree of relevance for South African media scholars. Primarily, thetheory investigates the relationship between the state and the media, an interconnection of profoundsignificance in the South African context, yet one that has not been explored sufficiently by scholars.This article, which focuses primarily on South Africa’s print media sector, sets out the parameters,major dimensions and some indicators of the Three Models paradigm. It then presents recentresearch in which the theory is applied to South Africa. It concludes that South Africa’s mediasystem falls largely into the Polarised Pluralist model though it retains strong liberal model traits